Developing and demonstrating inhibitory stimulus control over repetitive behavior. (20th February 2017) - Tiger, Jeffrey H.; Wierzba, Brittany C.; Fisher, Wayne W.; Benitez, Brittany B.
Abstract : Developing inhibitory stimulus control over repetitive behavior minimizes the social and learning disruptions caused by this behavior while allowing individuals to continue to access this source of reinforcement at nonproblematic times. These procedures involve allowing repetitive behaviors to occur in some stimulus conditions (S+) and blocking the repetitive behavior in order to disrupt the response–reinforcer relation in other stimulus conditions (S‐) such that the onset of the S‐ period results in rapid and sustained reductions in repetitive behavior. However, the demonstration of stimulus control exerted by the S‐ has often been confounded with participants' exposure to programmed reductive contingencies (i.e., behavior is reduced due to direct contact with contingencies rather than the programmed antecedent stimuli). The current study both developed and demonstrated the suppressive effects of S‐ presentation upon repetitive behavior with two children diagnosed with autism spectrum disorders. These demonstration techniques involved (a) introducing the S‐ into novel environments without the programmed contingencies that we used to establish discriminative control, (b) evaluating the reductive effects of programmed contingencies with and without the associated discriminative stimuli, and (c) evaluating latencies to the onset of repetitive behavior given S+ and S‐ presentations.